LEKSIKOLOGI SASTRA DALAM MANTRA CARA MENANAM TEMBUNI - NFR Casim Casim (Balai Bahasa Sulawesi Tengah, 2019)
Lexicology has a very important role in the study of spells, especially in the study of meaning (style). This paper focuses on: 1) the vocabulary used in the spell how to Cara Menanam Tembuni and translation; 2) mantra studies how to Cara Menanam Tembuni by examining meaning in language style. This type of research is descriptive qualitative research methods of text analysis. The data obtained are examined using descriptive analysis approach. From the results of a study on how to plant the placenta spells found: 1) the vocabulary used in the spell of how to grow the afterbirth is the Java Language Ngoko-Chromo among: meneng, jabang bayi, siro, beko, marang, bopo, biyung, sedulur, inggih; 2) spells by planting the placenta contained a tautolog-style parallelism assertion language (meneng-meneng, sugih-sugih, wani-wani, siro-siro, sedulur-sedulur, inggih inggih inggih; alliteration (meneng-meneng, wani-wani, sedulur-sedulur); and inversion (meneng-meneng jabang bayi siro).Keywords: Lexicology Literature, Mantra, Vocabulary, Meaning